Correction of neglected post-burn severe calcaneo-valgus deformity of foot with Joshi’s external stabilization system: a one stage surgical procedure - Mir, Faisal N.; Anika Adfar,; Mir, Naseer A. (International Journal of Research in Orthopaedics, 2023)
Post burn calcaneovalgus is a complex foot deformity and management becomes increasingly difficult especially if deformity is neglected in growing young child resulting in secondary bony deformity. A simple technique of single stage surgical correction with Joshi’s external stabilization system (JESS) is described using principle of distraction osteogenesis or histogenesis without need of extensive plastic surgical procedure. A functional plantigrade foot is achieved after completion of the procedure without need of any bony procedure and least chances of any neurovascular compromise. JESS is a versatile external fixation device for correction of neglected postburn complex calcaneovalgus deformity.